THE COLLEGE'S ACTIONS IN COUNTERACTING EDUCATIONAL EXCLUSION IN THE BHAVNAGAR REGION, INDIA ON THE EXAMPLE OF SWAMI SAHAJANAND COLLEGE OF COMMERCE AND MANAGEMENT - Lidia SHAHBAZYAN; Marek BOGUSZ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
In this article will be presented the phenomenon of educational exclusion in the context of the available literature, based on the example of one of the higher education institutions in India, compared to the Polish understanding of this occurrence. The structure of Indian higher education with the structural location of the college institution and its role in counteracting the above-mentioned phenomenon will also be presented.